Alzheimer's disease genetic risk variants beyond APOE ε4 predict mortality - Jesse Mez; Jessica R. Marden; Shubhabrata Mukherjee; Stefan Walter; Laura E. Gibbons; Alden L. Gross; Laura B. Zahodne; Paola Gilsanz; Paul Brewster; Kwangsik Nho; Paul K. Crane; Eric B. Larson; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2017)
Abstract Introduction We hypothesized that, like apolipoprotein E (APOE), other late‐onset Alzheimer's disease (LOAD) genetic susceptibility loci predict mortality. Methods We used a weighted genetic risk score (GRS) from 21 non‐APOE LOAD risk variants to predict survival in the Adult Changes in Thought and the Health and Retirement Studies. We meta‐analyzed hazard ratios and examined models adjusted for cognitive performance or limited to participants with dementia. For replication, we assessed the GRS‐longevity association in the Cohorts for Heart and Aging Research in Genomic Epidemiology, comparing cases surviving to age ≥90 years with controls who died between ages 55 and 80 years. Results Higher GRS predicted mortality (hazard ratio = 1.05; 95% confidence interval: 1.00–1.10, P = .04). After adjusting for cognitive performance or restricting to participants with dementia, the relationship was attenuated and no longer significant. In case‐control analysis, the GRS was associated with reduced longevity (odds ratio = 0.64; 95% confidence interval: 0.41–1.00, P = .05). Discussion Non‐APOE LOAD susceptibility loci confer risk for mortality, likely through effects on dementia incidence.